2014
DOI: 10.1007/s12288-014-0481-2
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer is an Effective Drug in Treating Hyperphosphatemia Due to Tumor Lysis Syndrome in Children: A Developing World Experience

Abstract: We report here a study on efficacy of sevelamer hydrochloride in treating hyperphosphatemia due to tumor lysis syndrome (TLS) in a developing world setting. Twenty one children with hyperphosphatemia due to TLS were included. All received hyper-hydration, allopurinol and sevelamer. Efficacy was assessed by decrease in serum phosphate level, calcium-phosphate product and TLS score as per Cairo Bishop definition. Four children who underwent dialysis were excluded from analysis. Among the remaining 17 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, a case report conducted by Harsha showed the effectiveness of sevelamer in treating hyperphosphatemia in two children with T-cell acute lymphocytic leukemia [ 9 ]. Another retrospective study by Kahlon et al found that sevelamer was effective in treating hyperphosphatemia caused by tumor lysis syndrome in 17 patients [ 10 ]. To our knowledge, this report represents the largest cohort of patients to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a case report conducted by Harsha showed the effectiveness of sevelamer in treating hyperphosphatemia in two children with T-cell acute lymphocytic leukemia [ 9 ]. Another retrospective study by Kahlon et al found that sevelamer was effective in treating hyperphosphatemia caused by tumor lysis syndrome in 17 patients [ 10 ]. To our knowledge, this report represents the largest cohort of patients to date.…”
Section: Discussionmentioning
confidence: 99%
“…Shaker and colleagues have performed a retrospective study in children with hematological malignancy and found that sevelamer is able to lower serum phosphate concentration over time significantly [8]. A couple of case studies have reported the effectiveness of the use of sevelamer in decreasing the serum phosphate level in children with/ without TLS, and they concluded that sevelamer is effective and prevents the need for hemodialysis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%